Local atomic structures of Gd and Zn atoms in extruded Mg-Gd-Zn alloys. (1st April 2021) - Zong, J.J.; Zhao, J.; Wang, X.D.; An, P.F.; Zhang, J.; Hu, T.D.; Cao, Q.P.; Zhang, D.X.; Jiang, B.; Jiang, J.Z.
Abstract: Minor addition of Gd and Zn can significantly improve the mechanical properties of extruded Mg-1 wt.%Gd-xZn ( x  = 0, 0.5, 1 wt.%) alloys. However, how they modify the structure of alloys remains elusive. By using x-ray absorption fine structure, we found that Zn atoms tend to bond with Gd and the 0.5 wt.% Zn addition greatly reduces the coordination number (CN) of Gd atoms, forming an enhanced double solid-solution strengthening. Whereas, 1 wt.% Zn not only increases the CNs of Zn and Gd but also promotes the formation of minor Mg3 Zn3 Gd2 phase. Compared with the grain refinement strengthening, it is found that the solid solution strengthening is not a dominant factor. Graphical abstract: Image, graphical abstract